Perspectives: Rationale and design of the ISACS-TC (International Survey of Acute Coronary Syndromes in Transitional Countries) project. (January 2014) - Bugiardini, Raffaele; Badimon, Lina; Manfrini, Olivia; ,; Boytsov, Sergei; Božidarka, Knežević; Daullxhiu, Irfan; Dilic, Mirza; Dorobantu, Maria; Erglis, Andreis; Gafarov, Valery; Gale, Christopher P.; et al.
Abstract: During the past 10 years, the health of people in Eastern Europe and the former Soviet Union has undergone changes very different from the health patterns seen in their Western counterparts. Mortality from cardiovascular disease has been decreasing continuously in the USA and many Western European countries, but it has increased or remained unchanged in many of the states of Eastern Europe. Analysis of this phenomenon has been hindered by insufficient information. The International Registry of Acute Coronary Syndromes registry study in Transitional Countries (ISACS-TC) is both a retrospective—over a 1-year period—and prospective study which was designed in order to obtain data of patients with acute coronary syndromes (ACSs) in countries with economy in transition in Central and Eastern Europe, and herewith control and optimize internationally guideline recommended therapies in these countries. Adhesion to the project was given by 112 Collaborating Centres in 17 countries with economy in transition (Albania, Bosnia and Herzegovina, Belarius, Bulgaria, Croatia, Hungary, Kosovo, Latvia, Lithuania, Macedonia, Moldova, Montenegro, Romania, Russian Federation, Serbia, Slovakia, Slovenia, and Ukraine). A total of 47 cluster sites in 11 countries in Central and Eastern Europe are currently collaborating in ISACS-TC. The registry encourages optimal individualization of evidence-based therapies and the international patient body ensures good representation of multiple practice patterns. It may help to make an additional improvement in clinical outcomes of countries with economy in transition.